Organizational Culture and Management of Institutional Repositories of University Libraries in Southwest Nigeria (Lead City International Journal of Library, Information & Communication Sciences, 2025)
Academic libraries rely on organisational culture to manage daily operations effectively. The Denison Model of Organizational Culture, known for its comprehensive management dimensions, offers unexplored potential in institutional repository (IR) management. This study utilised a descriptive survey design to investigate the impact of involvement, consistency, and adaptability - key indicators of organisational culture - on managing IR in Southwest Nigerian university libraries. The study targeted 352 library personnel from 14 university libraries that had established institutional repositories. Total enumeration sampling was used to include all 352 personnel. A structured questionnaire containing 36 items, evenly distributed across the Denison Model's three dimensions, was used for data collection. Of the 352 questionnaires distributed, 298 were returned, and 246 valid responses were analysed, representing a 70% response rate. Descriptive and inferential statistics, comprising frequency, percentage, mean, and simple linear regression, provided insights into the relationship between organisational culture and IR management. The findings highlighted the significant influence of involvement, consistency, and adaptability in shaping IR operations. The study recommends strengthening these dimensions and their associated traits to enhance IR management, improve library efficiency, and align with modern academic and technological demands.